Naravne, gospodarske, politične in demografske danosti Trente v Triglavskem narodnem parku - Simonič, Peter (Traditiones (Ljubljana), 2013)
The Trenta Valley lies in the Julian Alps and has a rich and turbulent history, even though tourists may feel like time has stood still there. This article defines five basic organizational development phases or paradigms to evaluate the valley's relation to surrounding Triglav National Park. The premise used is not modernist, heritage-oriented, or folklorist (unidirectional development and structure), but is based on culture and ecology (multidirectional development and process).
Keywords: ethnology; Kulturna dediščina; folk culture; Naravna dediščina; Narodni parki; cultural heritage; natural heritage; Trenta; Triglavski narodni park; tourism; Etnologija; Ljudska kultura; Slovenska ljudska kultura; Turizem; Triglav National Park